MICROORGANISMS AND MICROBIOTA: A BIBLIOMETRIC STUDY OF CURRENT LITERATURE - Fernandes de Oliveira, Marcos; Frederico de Souza Castro, Carlos; Coelho da Cruz, Danielle; Gonçalves Sales Assunção, Simone; Martins da Silva Fernandes de Oliveira, Rebeca (Journal of Interdisciplinary Debates, 2025)
The actions of microorganisms in the soil are diverse and extremely important for the maintenance of their physical and chemical characteristics. The total or partial degradation of xenobiotic substances present in the soil through the processes of phytoremediation and bioremediation. The objective of this study is to present a bibliometric analysis of the biogeochemical cycle, microfauna and microbiota present in soils using the Rstudio software, an updated “radiography” of the literature. The methodological protocol followed for this research was the survey of the “Scopus” and “Web of Science” databases. The search expressions (“microbiological action”) OR (“fungi”) OR (“yeast”) OR (“bacteria”) OR (“enzymatic action”) AND (“soils”) OR (“agricultural soils”) OR (“soil physical characteristics”) OR (chemical characteristics”) AND (“soil biogeochemical cycle”) were used, applying the following filters: scientific articles, from the last five years (2020-2025), in English, in soil science, with a minimum citation index of 3.5. A total of 1,981 articles were retrieved from Scopus and 1,041 from the Web of Science, totaling 3,022 papers. After the exclusion of 742 duplicate articles, 2,280 unique works were generated, which make up this bibliometric analysis on the subject. The relationship indicated by this bibliometric analysis between the soil and the microbiome is broad, complex, necessary and constant. Whether in the degradation of organic or inorganic compounds, xenobiotic compounds or in the maintenance of the physical characteristics of soil profiles. However, research faces a major challenge in terms of understanding the metabolic mechanisms of these individuals in terms of their reproduction and the metabolic products generated.